Implementasi QR Code Dalam Sistem Presensi pada Percetakan Global Graphic - Thannia, Yvonne; Antonius, Antonius; Willay, Thommy (Universitas Multi Data Palembang, 2025)
With the development of information technology, the employee attendance recording system at Global Graphic Printing is still done manually, which has the potential to cause inaccuracy and lack of detail in the resulting reports. This study aims to develop a responsive web-based attendance system by utilizing QR Code technology, so that it can be accessed directly through each employee's device. The methods applied include system development using the waterfall method and QR Code-based system design integrated with a web platform and MySQL database, allowing real-time attendance recording. In its development, this study uses Unified Modeling Language (UML) modeling. The attendance system is designed using Android Studio with PHP, HTML, JavaScript, and CSS programming languages. The implementation of this system is expected to reduce manual recording errors, speed up the attendance process, and increase report transparency. Thus, this system has the potential to increase company productivity and create a more organized work environment.